2021
DOI: 10.1055/a-1403-2606
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Achilles Tendon Mechanics on the Running Economy of Elite Endurance Athletes

Abstract: The Achilles tendon stores and releases strain energy, influencing running economy. The present study aims to verify the influence of the Achilles tendon tangent modulus, as a material property, on running economy by comparing two groups of elite endurance-performance athletes undergoing different running training volumes. Twelve athletes, six long-distance runners and six pentathletes, were studied. Long-distance runners had a higher weekly running training volume (116.7±13.7 vs. 58.3±20.4 km, p<0.05) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 40 publications
0
9
2
Order By: Relevance
“…A stronger muscle with shorter fascicles will demand a higher tendon mechanical capacity (i.e., higher stiffness), which is probably related to an improvement in the operating fascicle force-velocity profile, mainly during the tendon lengthening, improving the muscular work production efficiency ( Bohm et al, 2021a ). A stiffer Achilles tendon may reach higher elastic energy storage and release capacity ( Pinto et al, 2021 ). As the runners present similar Achilles tendon strain during running compared to the non-runners and the runners with different running economies ( Rosager et al, 2002 ; Arampatzis et al, 2006 ), a larger Achilles tendon CSA will require a greater amount of force to stretch the tendon, increasing the elastic strain energy stored ( Rosager et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A stronger muscle with shorter fascicles will demand a higher tendon mechanical capacity (i.e., higher stiffness), which is probably related to an improvement in the operating fascicle force-velocity profile, mainly during the tendon lengthening, improving the muscular work production efficiency ( Bohm et al, 2021a ). A stiffer Achilles tendon may reach higher elastic energy storage and release capacity ( Pinto et al, 2021 ). As the runners present similar Achilles tendon strain during running compared to the non-runners and the runners with different running economies ( Rosager et al, 2002 ; Arampatzis et al, 2006 ), a larger Achilles tendon CSA will require a greater amount of force to stretch the tendon, increasing the elastic strain energy stored ( Rosager et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is interesting as trained runners present higher Achilles tendon stiffness compared with healthy non-runners ( Devaprakash et al, 2020 ). Furthermore, Pinto et al (2021) found that the Achilles tendon material (maximum tangent modulus and stress) of elite long-distance runners ( N = 6) is higher than that of pentathletes ( N = 6). Moreover, the authors suggest that higher Achilles tendon stiffness is presumably associated with the highest weekly running training volume and with a tendency to reach higher elastic energy storage and release capacity.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations